Who are you and why are you here? : tales of international development - Claessens, Jacques, 1928-2012 (Between the Lines, 2018)
"Every international development project looks good on paper until someone asks, "Who are you and why are you here?" In this case, it's a man from northern Burkina Faso. His question reveals everything wrong with international development work today. Jacques Claessens questions the real effects of development programs and agencies, NGOs, and multinational corporations on the economy and welfare of the global south--from a Kafkaesque well-drilling project in Udathen to the Chernobyl-like environmental devastation wrought by the Canadian-owned Essakane mine. Through tales of uneasy encounters between nomadic Tuaregs and Western engineers, well-meaning NGO staff and their incredibly self-serving bosses, UN bureaucrats, a greedy Canadian mining company, and Burkinabe villagers--all pursuing ostensibly noble goals, all barely listening to each other--we begin to understand the realities of international development."--